Hemicolectomy versus appendectomy for patients with appendiceal neuroendocrine tumours 1–2 cm in size: a retrospective, Europe-wide, pooled cohort study. Issue 2 (February 2023) - Nesti, Cédric; Bräutigam, Konstantin; Benavent, Marta; Bernal, Laura; Boharoon, Hessa; Botling, Johan; Bouroumeau, Antonin; Brcic, Iva; Brunner, Maximilian; Cadiot, Guillaume; Camara, Maria; Christ, Emanuel; et al.
Summary: Background: Awareness of the potential global overtreatment of patients with appendiceal neuroendocrine tumours (NETs) of 1–2 cm in size by performing oncological resections is increasing, but the rarity of this tumour has impeded clear recommendations to date. We aimed to assess the malignant potential of appendiceal NETs of 1–2 cm in size in patients with or without right-sided hemicolectomy. Methods: In this retrospective cohort study, we pooled data from 40 hospitals in 15 European countries for patients of any age and Eastern Cooperative Oncology Group performance status with a histopathologically confirmed appendiceal NET of 1–2 cm in size who had a complete resection of the primary tumour between Jan 1, 2000, and Dec 31, 2010. Patients either had an appendectomy only or an appendectomy with oncological right-sided hemicolectomy or ileocecal resection. Predefined primary outcomes were the frequency of distant metastases and tumour-related mortality. Secondary outcomes included the frequency of regional lymph node metastases, the association between regional lymph node metastases and histopathological risk factors, and overall survival with or without right-sided hemicolectomy. Cox proportional hazards regression was used to estimate the relative all-cause mortality hazard associated with right-sided hemicolectomy compared with appendectomy alone. This study is registered with ClinicalTrials.gov, NCT03852693 . Findings: 282 patients with suspected appendiceal tumours were identified, of whom 278 with an appendiceal NET of 1–2 cm in size were included. 163 (59%) had an appendectomy and 115 (41%) had a right-sided hemicolectomy, 110 (40%) were men, 168 (60%) were women, and mean age at initial surgery was 36·0 years (SD 18·2). Median follow-up was 13·0 years (IQR 11·0–15·6). After centralised histopathological review, appendiceal NETs were classified as a possible or probable primary tumour in two (1%) of 278 patients with distant peritoneal metastases and in two (1%) 278 patients with distant metastases in the liver. All metastases were diagnosed synchronously with no tumour-related deaths during follow-up. Regional lymph node metastases were found in 22 (20%) of 112 patients with right-sided hemicolectomy with available data. On the basis of histopathological risk factors, we estimated that 12·8% (95% CI 6·5 –21·1) of patients undergoing appendectomy probably had residual regional lymph node metastases. Overall survival was similar between patients with appendectomy and right-sided hemicolectomy (adjusted hazard ratio 0·88 [95% CI 0·36–2·17]; p=0·71). Interpretation: This study provides evidence that right-sided hemicolectomy is not indicated after complete resection of an appendiceal NET of 1–2 cm in size by appendectomy, that regional lymph node metastases of appendiceal NETs are clinically irrelevant, and that an additional postoperative exclusion of metastases and histopathological evaluation of risk factors is not supported by the presented results. These findings should inform consensus best practice guidelines for this patient cohort. Funding: Swiss Cancer Research foundation.